Pengaruh Retribusi Daerah dan Dana Alokasi Khusus Terhadap Belanja Modal Pada Kabupaten/Kota di Provinsi Jawa Barat - Suryanti, Maria Yenivadia; Halimah, Imar (Prisani Cendekia, 2025)
This study aims to determine and analyze the effect of blood levy and Special Allocation Fund (DAK) on capital expenditure. This study uses a sample of districts / cities in West Java Province contained in the Central Statistics Agency (BPS) in 2019-2023. The sample technique used was purpose sampling, where from 27 districts / cities a sample of 18 districts was obtained for 5 years so that a total of 90 data samples were obtained. The analysis used is panel data regression analysis using a fixed effect model. The results obtained show that simultaneously local retribution and the Special Allocation Fund have a significant effect on capital expenditure. Personally, local retribution and Special Allocation Fund have a positive and significant influence on capital expenditure